Analisis Terhadap Kedudukan Peraturan Desa Dalam Sistem Peraturan Perundang-Undangan Di Indonesia - Okta Lipana (Indragiri Law Review, 2025)
Village government is a national government system that is directly in the regions. The reform era gave birth to the idea of ​​granting autonomy to villages as the smallest part of the state government. This research is a normative legal research, using a statute approach, examining the relevant laws and regulations in terms of the position of Village Regulations. The regulation of village regulations and the mechanism for their formation are regulated in their implementing regulations. The village law has provided lex specialis for village regulations so that their presence is now a necessity in a village government.